Joint manifestations revealing inborn metabolic diseases in adults: a narrative review - Amaury Loret; Claire Jacob; Saloua Mammou; Adrien Bigot; Hélène Blasco; Alexandra Audemard-Verger; Ida VD Schwartz; Denis Mulleman; François Maillot (Orphanet Journal of Rare Diseases, 2023)
Abstract Inborn metabolic diseases (IMD) are rare conditions that can be diagnosed during adulthood. Patients with IMD may have joint symptoms and the challenge is to establish an early diagnosis in order to institute appropriate treatment and prevent irreversible damage. This review describes the joint manifestations of IMD that may be encountered in adults. The clinical settings considered were arthralgia and joint stiffness as well as arthritis. Unspecific arthralgias are often the first symptoms of hereditary hemochromatosis, chronic low back pain may reveal an intervertebral disc calcification in relation with alkaptonuria, and progressive joint stiffness may correspond to a mucopolysaccharidosis or mucolipidosis. Gaucher disease is initially revealed by painful acute attacks mimicking joint pain described as “bone crises”. Some IMD may induce microcrystalline arthropathy. Beyond classical gout, there are also gouts in connection with purine metabolism disorders known as “enzymopathic gouts”. Pyrophosphate arthropathy can also be part of the clinical spectrum of Gitelman syndrome or hypophosphatasia. Oxalate crystals arthritis can reveal a primary hyperoxaluria. Destructive arthritis may be indicative of Wilson’s disease. Non-destructive arthritis may be seen in mevalonate kinase deficiency and familial hypercholesterolemia.